Short history of economic progress - "Brenner, Y. S." (London, 1969)
This book is based upon a series of lectures on the history of economic development given to students of economics at Cape Coast University in Ghana. It aims at providing an analysis of economic progress in the developed countries which will show which geo-economic, social, political and cultural forces assisted such progress, and which forces delayed or hindered it. It should incidentally explain why European nations took several decades to emulate the economic and industrial achievements of Britain; why nations in other parts of the world (e.g. Japan and Russia) were unable for a considerable time to match the advances of Western Europe and the United States, and why the developing countries are at present finding it so difficult to catch up with the economic progress of the more advanced industrial nations.
Keywords: Economic history